Life and the dignity of the human – from when and until when . Current challenges for the European Christian identity - Meuwissen, Sébastien (The phenomenon of euthanasia: Philosophy – Culture – Medicine – Law, 2025)
For several decades, countries of the broadly understood West have been characterized by a growing tendency to redefine certain concepts in the field of the right to life and the way of understanding human dignity. Such phenomena as high eugenics or preferential utilitarianism lead to the deprivation of the indisputable right to life of some people on the basis of increasingly subjective premises. The distinction between “people” and persons is de facto associated with the dehumanization of, for example, unborn children and some members of society. Contrary to this trend, it is crucial to use precise vocabulary and substantive argumentation in the debate around the issue of the protection of life. The more so that in some countries of our civilization, an honest and reliable debate around, for example, abortion or euthanasia is becoming more and more difficult due to the ubiquitous political correctness.